Progress and Performance of Kisan Credit Card (KCC) Scheme in India Since 1998 - Sharma, Chaman Prakash; Singh, Aditya (Journal of Commerce and Trade, 2020)
Government of India has taken several steps in the context of agriculture credit. Credit is essential for the development of agriculture in India. Since most of the Indian farmers are marginal farmers, therefore they are not able to invest huge amount of money for the betterment of agriculture. Thus, they remain marginal farmers throughout their life. In order to solve this problem, NABARD launched Kisan Credit Card (KCC) scheme in 1998 for smooth flow of agriculture credit. The scheme was implemented across the country in all the states and union territories by the public sector Commercial Banks, Regional Rural Banks (RRBs) and Cooperative banks. This study mainly pertains to the agency-wise and period-wise progress of KCC Scheme. The study reveals a significant increase in the number of cards issued in each year by different agencies. So it may be concluded that the banking sector promote KCC scheme efficiently and enhance hassle free credit delivery mechanism to agriculture sector.